2011
DOI: 10.1098/rspa.2011.0226
|View full text |Cite
|
Sign up to set email alerts
|

Steady-state propagation of dislocations in quasi-crystals

Abstract: We analyse the steady propagation at constant speed, lower than the shear wave-speed, of a straight dislocation in an unbounded elastic quasi-crystal with five-fold symmetry. We discuss only the ideal elastic behaviour, neglecting the dissipation associated with the atomic rearrangements. Under these conditions, we provide the expressions of phonon and phason fields in closed form. Both phonon and phason stresses appear to be singular near to the dislocation core. We also find the explicit expression of the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 25 publications
(49 reference statements)
0
17
0
Order By: Relevance
“…On the other hand, the values of the materials can be approximately estimated by referring to the results associated with isotropic QCs. Such a purpose can be fulfilled in view of the results available in the literature [32,[41][42][43][44][45][46]. It has been reported that the Lamé constants of AlPdMn, a special kind of icosahedral QC, are reported to be λ 0 = 85 GPa and μ 0 = 65 GPa [42], and that the ratio between the phonon-phason coupling coefficient and the shear modulus R i /μ 0 is approximately 0.03 [44].…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, the values of the materials can be approximately estimated by referring to the results associated with isotropic QCs. Such a purpose can be fulfilled in view of the results available in the literature [32,[41][42][43][44][45][46]. It has been reported that the Lamé constants of AlPdMn, a special kind of icosahedral QC, are reported to be λ 0 = 85 GPa and μ 0 = 65 GPa [42], and that the ratio between the phonon-phason coupling coefficient and the shear modulus R i /μ 0 is approximately 0.03 [44].…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…As a consequence, numerical analysis can be readily performed, once the values of the material constants are available. However, owing to the absence of the experimental data, especially those characterizing interactions between phonon and phason fields [2,32], such a goal seems not to be achieved. On the other hand, the values of the materials can be approximately estimated by referring to the results associated with isotropic QCs.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, the phonon-phason elasticity of QCs has attracted a lot of attention too. For example, Radi and Mariano have described linear elasticity of QCs, and obtained some meaningful results for the straight cracks and dislocations in two-dimensional quasicrytals [36][37][38]. An important reference concerning fundamental aspects of generalized elasticity and dislocation theory deriving the generalized three-dimensional elastic Green tensor and all the dislocation key-formulas including an application to dislocation loops for arbitrary quasicrytals is presented by Lazar and Agiasofitou [39].…”
Section: Introductionmentioning
confidence: 99%